EYE GAZE TRACKING SYSTEM FOR ADAPTED HUMAN-COMPUTER INTERFACE - Santos, Rafael Lopes (2017)
This work describes the implementation of an eye gaze tracking system for a natural user interface, based only on non-intrusive devices, like Intel RealSense camera. Through image processing, the implemented system is able to convert face elements to the corresponding focus point on the computer screen. Tests show promising results.